RESPON AL-QURAN TERHADAP KARAKTER ORANG FASIK - Hafizullah, Hafizullah; Wijayanti, Tri yuliana; Juliarti, Rosiska (Majalah Ilmu Pengetahuan dan Pemikiran Keagamaan Tajdid, 2020)
This research is based on the fact that many people who know the science of religion and claim to believe in Allah SWT and His Messenger, but not a few of them violate the rules of Allah SWT and commit ungodliness. The objectives of this study are: (1) to describe and analyze the character of the wicked according to the Koran, and (2) to explain and analyze how to deal with / overcome them. This type of research is library research (library research). The analytical method used in this study is the thematic interpretation method or Maudhu’i. The data collection technique that I use is to use al-Mu'jam al-Mufahras li Alfazh Alquran al-Karim. Data processing is done by classifying verses about the wicked, then processed and explored their interpretation by referring to the existing commentaries, and explain through effective sentences. The results of this study are that there are seven characteristics of the wicked, namely: 1) a person who is misled by God Almighty, 2) reneges on the verses of Allah, 3) turns away after promising to Allah, 4) the heinous and evil people, 5 ) their hearts are hard, 6) making up lies, 7) forgetting Allah Almighty. While there are three ways to deal with the wicked, namely: first examine the news brought by the wicked, and not receive a testimony from the wicked, and do not ask for forgiveness for the wicked.